Changes in HIV knowledge, and socio-cultural and sexual attitudes in South India from 2003-2009 - Bradley Janet; Rajaram S; Moses Stephen; Bhattacharjee Parinita; Lobo Anil M; Ramesh BM; Washington Reynold; Alary Michel (BMC, 2011)
Abstract Background As communities face serious pressures on traditional values, such as those posed by HIV infection, cultural inertia may result, whereby existing trends towards more liberalized views of sexuality are stalled. We examined changes in attitudes around HIV in Bagalkot district, south India, between 2003 and 2009. Methods General population surveys were conducted in 2003 and 2009, among approximately 6,600 randomly sampled men and women in 10 villages and 20 urban blocks of Bagalkot. Questions about HIV knowledge, sexuality, gender and condoms were included. We compared responses in the two surveys using a multivariate logistic regression model. Results Awareness of HIV increased significantly from 76.9% in 2003 to 87.8% in 2009, and condom awareness increased significantly (37.4% to 65.4%) in all groups studied. However, in 2009, only 23% of people mentioned condoms as a means of prevention, an improvement from 8% in 2003 (adjusted odds ratio (AOR) 3.3; 95%CI 2.6-4.1, p <0.001). There was a significant increase in the number of women believing sex workers should be compulsorily tested for HIV (76.3%-86.4%%, AOR 1.8; 95%CI 1.4-2.4, p<0.001). An increasing number agreed that "it is wrong to talk about sex" (p=0.05), especially women (21.9% vs. 32.4%, p<0.01). There was an increase in women who thought it "wrong to talk about AIDS in a respectable family", and more respondents in 2009 thought it improper to discuss condoms (15.6% vs. 27.4%, AOR 1.9, 95%CI 1.4-2.8, p=0.001). In 2003, 31.4% agreed that "access to condoms promotes promiscuity", increasing to 45.2% in 2009 (AOR 1.7; 95%CI 1.3-2.3, p<0.001). Educated and young urban women were the most likely to believe this. In 2003, 19.3% and in 2009 30.2% (AOR 1.8, 95%CI 1.4-2.3, p<0.001) thought that sex education promotes sexual activity and promiscuity. Conclusions Despite increases over time in HIV-related knowledge and reductions in stigmatizing attitudes, resistance to changing cultural mores was apparent, with less willingness to embrace openness and discuss sexuality. Young and female respondents appeared to be the most resistant to change, reflecting a cultural inertia that mirrors studies of other pressures on traditional societal values. More effort is required to advocate among women and young people for healthy sexuality, openness and safe sex practices.